Student-centred instruction in science and technology: a model of factors at organizational and individual levels - Petra Pejić Papak; Milena Valenčič Zuljan; Darjo Zuljan (University of Maribor Press, 2021)
To achieve the goals of modern science and technology teaching, it is vital to organize student-centred instruction (SCI). The organization of SCI requires the teacher's ability to organize cognitively challenging teaching in a stimulating environment. The fundamental purpose of the study was to determine whether the teacher's organization of SCI was related to factors at the school level (organizational context) and factors at the individual level (individual context). We designed a model comprising four sets of factors. The results show a statistically significant correlation between SCI and all four sets of factors.